Sex testing : gender policing in women's sports - Pieper, Lindsay Parks, 1985- (Sport and society., 2016)
"In 1968, the International Olympic Committee (IOC) implemented sex testing for female athletes at that year's Games. When it became clear that testing regimes failed to delineate a sex divide, the IOC began to test for gender --a shift that allowed the organization to control the very idea of womanhood. Lindsay Parks Pieper explores sex testing in sport from the 1930s to the early 2000s. Focusing on assumptions and goals as well as means, Pieper examines how the IOC in particular insisted on a misguided binary notion of gender that privileged Western norms. Testing evolved into a tool to identify--and eliminate--athletes the IOC deemed too strong, too fast, or too successful. Pieper shows how this system punished gifted women while hindering the development of women's athletics for decades. She also reveals how the flawed notions behind testing--ideas often sexist, racist, or ridiculous--degraded the very idea of female athleticism"--